The Effect of Company Size, Industry Classification, and Audit Tenure on Audit Report Lag - Rachman, Helmy Aulia; Astri, Mutia Fadila (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to empirically prove the effect of company size, industry classification, and audit tenure on audit report lag with complexity of operations as moderating variable of State or Regional Owned Enterprises (Badan Usaha Milik Negara/Daerah/BUMN/D) companies listed on the Indonesian Stock Exchange in 2020-2022. This study employs quantitative approach involving secondary data of the companies’ annual report published on the official website of the Indonesia Stock Exchange collected through documentation. The samples selected through purposive sampling method include 111 observational data analyzed by multiple linear regression and moderated regression analysis. The results of the study show that company size has a negative effect and industry classification has a positive effect on audit report lag, with complexity of operations being able to moderate the effect of both variables. However, the results of this study cannot prove the existence of an effect between audit tenure and audit report lag, and complexity of operations is unable to moderate the effect of audit tenure on audit report lag.